Endogenous resources and tourism development in the Department of Valle (Honduras) - Bonilla-Rodríguez, Stephany Dashiell; Hortelano-Mínguez, Luis Alfonso (Revista de Estudios Andaluces, 2023)
The Department of Valle is situated at the southern edge of Honduras and with neighbouring Choluteca it shares the Pacific coast on the Gulf of Fonseca. Socioeconomic and demographic data indicate the area’s backwardness and poverty for which it is often labelled as part of ‘deep Honduras’ or according to some researchers as ‘the South of the South’. The aim of this study is to analyse the interlocking spheres of natural and cultural resources and the potential for tourism development that may contribute to the generation of wealth in situ. The research methods consist of primary and secondary data, mapping and direct observation during fieldwork. The study reveals a potential for sun and beach tourism, ecotourism, adventure and sports tourism. Exploiting the potential offers employment opportunities for natives and provides a complement to the existing means of subsistence.